2023
DOI: 10.1002/tox.23892
|View full text |Cite
|
Sign up to set email alerts
|

NIK‐mediated reactivation of SIX2 enhanced the CSC‐like traits of hepatocellular carcinoma cells through suppressing ubiquitin–proteasome system

Abstract: The critical roles of NF‐κB Inducing Kinase (NIK) in tumor progression have been elucidated in various tumors; however, its effects on hepatocellular carcinoma (HCC) progression are still confusing. Here, we found that NIK level was upregulated in HCC tissues compared to that of normal tissues, and positively correlated with the levels of cancer stem cell (CSC) markers. Then we established HCC cells with NIK‐stable knockdown and found that NIK knockdown suppressed the CSC—like traits of HCC cells through in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additionally, research has revealed upregulation of NIK expression in HCC tissues and cells. Knockdown of NIK reduces the cancer stem cell-like characteristics of HCC cells 36 . These findings offer important clues for further understanding the role of NIK in disease progression and developing relevant therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research has revealed upregulation of NIK expression in HCC tissues and cells. Knockdown of NIK reduces the cancer stem cell-like characteristics of HCC cells 36 . These findings offer important clues for further understanding the role of NIK in disease progression and developing relevant therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%